Efficacy of simethicone for treatment of bloat in ruminants (Asian Journal of Medical and Biological Research, 2017)
The objective of the study was to evaluate the efficacy of simethicone against bloat in ruminants. The investigation was conducted in Potiya Upazila under the Chittagong district where routine veterinary services were in operation by the Community-based Dairy Veterinary Foundation (CDVF), Bangladesh Agricultural University, Mymensingh, Bangladesh. The diagnosis of bloat in animals was done based on clinical history, clinical signs and examination of animals. A total of 90 ruminants (60 cattle, 10 sheep and 20 goats) affected with bloat were treated with simethicone containing two commercial products marketed in Bangladesh (One product such as Bloat Stop®, marketed by ACME Laboratories, Bangladesh and another imported product by other pharmaceutical company). For treatment, 1 gm simethicone in 100 ml solution in cattle and 200 mg simethicone in 20 ml solution in sheep and goats were administered once at a time. The efficacy of simethicone from two commercial products was evaluated on the basis of recovery rate of affected animals. The overall recovery rates in ruminants after treatment with Bloat Stop® and other commercial product were 80% and 76%, respectively. In cattle recovery rate was numerically higher (83%) when treated with commercial product than that of other product (80%). In sheep, recovery rate was numerically higher (80%) when treated with Bloat Stop® than that of imported product (60%). In goats, the recovery rate was 70% after treatment of bloat with both products. However, the recovery rates in ruminant did not differ statistically between two drugs used for treatment of bloat (p>0.05). In conclusion simethicome is an effective drug for clinical treatment of bloat in ruminants.Asian J. Med. Biol. Res. December 2016, 2(4): 635-638